2012
DOI: 10.1152/ajpendo.00661.2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal metabolism and parental genetics on fetal maldevelopment in diabetic rat pregnancy

Abstract: The purpose of this study was to investigate the influence of parental transgenerational genetics and maternal metabolic state on fetal maldevelopment in diabetic rat pregnancy. Rats from an inbred malformation-resistant (W) strain, and an inbred malformation-prone (L) strain, were cross-mated to produce two different F(1) hybrids, WL and LW. Normal (N) and manifestly diabetic (MD) WL and LW females were mated with normal males of the same F(1) generation to obtain WLWL and LWLW F(2) hybrids. Maternal diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…These malformations are related to defects in the fetal expression of developmental genes such as bone morphogenetic protein 4 and the sonic hedgehog gene and those that encode enzymes for the management of reactive oxygen species, which shows that glucose has a teratogenic effect at several levels. 18 However, there have been some controversial results. Some reports have found that diabetic mothers have an increased risk of having a child with cleft lip and palate compared with non-diabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
“…These malformations are related to defects in the fetal expression of developmental genes such as bone morphogenetic protein 4 and the sonic hedgehog gene and those that encode enzymes for the management of reactive oxygen species, which shows that glucose has a teratogenic effect at several levels. 18 However, there have been some controversial results. Some reports have found that diabetic mothers have an increased risk of having a child with cleft lip and palate compared with non-diabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with either pre-gestational diabetes mellitus (PGDM) or gestational diabetes mellitus are at high risk (2–5 times higher than non-diabetic pregnancies) of carrying a fetus with congenital anomalies, such as phocomelia, cardiac malformations, macrosomia and central nervous system malformations [ 1 , 2 ]. Among those congenital malformations induced by hyperglycemia, congenital heart disease [ 3 ] and anomalies of the nervous system are prominent [ 4 ] because both the cardiovascular and nervous systems start to develop during the early embryonic developmental stage, the period that is vulnerable to external harmful factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that fetal cardiac defects are closely associated with maternal hyperglycemia because they occur up to 5 times more often in pre-gestational diabetic mothers compared to those without diabetes. 1 There are many types of rodent animal models that have been employed to date to explore the mechanism of diabetic teratogenesis. Based on the characteristics Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of congenital malformations in diabetic pregnancy has been reported to be 2-5 times higher than in non-diabetic pregnancy. 1 Therefore, pregnant women with preexisting diabetes mellitus or gestational diabetes are at high risk of carrying a fetus with congenital anomalies such as neural phocomelia, cardiac malformations, macrosomia and central nervous system malformations. 2 Macintosh et al reported that the increased risk of congenital anomalies was predominantly for congenital heart disease (3.4 times higher risk) and anomalies of the nervous system (2.7 times higher risk) in their study.…”
Section: Introductionmentioning
confidence: 99%